Islamic Law in German courts - Rohe, Mathias (Hawwa, 2003)
The application of Islamic law in a Western country-enforced by Western courts-may cause considerable irritation among many citizens in our countries. There are well-known issues of tension between traditional Islamic rules, especially those relating to Family law, and Western legal convictions. Nevertheless, Islamic law is indeed generally applicable in Germany on two levels. The rules of German Private International Law may lead to such a result; furthermore, an area of-indirect-application opens up within the framework of the so-called "optional" civil law. The task of German courts in such cases is to clarify the limits of public order (public policy) which may prevent the application of provisions contrary to the German legal standard of human rights. After having defined the levels of application of Islamic law in Germany, this article focuses on the Germany court practice concerning "critical" issues of Family law such as the rules on marriage, divorce, maintenance, guardianship, custody and adoption. © 2003 Koninklijke Brill, Leiden.
UnivIS-Import:2015-03-09:Pub.2003.rw.recht.IZZ.LZZA.islami